KEAHLIAN AUDITOR INTERNAL DALAM MENDETEKSI FRAUD PADA PT INTI DRAGON SURYATAMA - Putra Wiyandika, Shindy Permana; Ardini, Lilis (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is aimed to find out the skills and the abilities of internal auditor and to find out theabilities of internal auditor in detecting fraud at PT Inti Dragon Suryatama. The research method hasbeen done by using qualitative method because this research is not meant to prove a hypothesiswhereas the data analysis technique has been carried out by using descriptive analysis quanlitativeapproach. Based on the result of the analysis and the discussion, fraud can be anticipated by goodinternal control. In order to support internal auditor in uncovering fraud which has occurred at PTInti Dragon Suryatama the skills which conform to professional standards of internal auditing (SPAI)which are categorizeed into three factors: communication ability, creativity and able to work withother people. In conducting the purchase transaction recording which has been made by PT IntiDragon Suryatama, the fraud element has been found by internal auditor, it can be seen from thepurchase transaction of EVA goods and plastics. The skills of internal auditor which have been used touncover the fraud which occur at PT Inti Dragon Suryatama have been conformed to Professionalstandards of Internal Auditing.Keywords : skills, auditor internal, fraud.